Inovasi Bahan Ajar Dinamika Gerak dengan Modul Pembelajaran Berbasis Discovery Learning - Siti Halimatul Fatihah; Neng Nenden Mulyaningsih; Irnin Agustina Dwi Astuti (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2020)
Physics learning with discovery learning approach requires students to be active in learning. In th schools in tangerang area, there is no discovery learning module available. the purpose of this research is to develop a physics learning module based on discovery learning on Motion materials. This research method is research & development with ADDIE model (analyze, design, development, implementetion, evaluation), using research instruments in the form of validation sheets. the data analysis technique used is descriptive analysis. The results of the study showed that discovery learning-based physics learning modules are worth testing and implementing to students. This module has characteristics according to discovery learning syntax and user friendly so that students can learn independently.